ASEAN centrality amid increasing global multipolarity - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2024)
The Association of Southeast Asian Nations is considered as one of the successful regional cooperations and has played a remarkable role in regional, and potentially global, order through its principles of consensus, non-interference, and peaceful resolution of conflicts, providing platform for dialogue both among its members and external partners. Crucial to its architecture is the ASEAN centrality, the principle that directs ASEAN to be at the center of every mechanism and discussion concerning political, security, and economic issues, among others. Over the years, however, regional and global developments have thrown some weights over the region, leaving the credibility of ASEAN's centrality in question. For instance, the global order, which is once thought to be aligned to a unipolar authority, the United States, is increasingly exhibiting the characteristics of a multipolar world, with the emergence of stronger and more independent economies. To understand how the increasing global multipolarity influences ASEAN, this paper investigates how the shifting global geopolitical landscape, characterized by power rivalries and economic interdependence, influences ASEAN in its central role in regional affairs. The study highlights the varied short-term geopolitical influences that diminish over time, emphasizing the need for ASEAN and the Philippines to strengthen regional integration, diversify partnerships, and balance external relations to maintain and sustain resilience and leadership in the region.
Keywords: 330; ASEAN; centrality; cooperation; free trade; geopolitics; globalization; influence; integration; international relations; international trade; multipolarity; polar; power; regional cooperation; regional economy